NDP HMI Concept in AnsweringSocial, Economic and Political Problems - Muhammad Yusuf Muda Azka (Journal of Strategic Innovation in Economics and Business, 2025)
This research examines the role of the Basic Values ​​of Struggle (NDP) of the Islamic Student Association (HMI) in responding to social, economic and political problems in Indonesia. Using the literature review method, this research analyzes various literature sources related to the implementation of the NDP HMI in the context of national development. The research results show that the NDP HMI has made significant contributions in three main aspects. First, in the social aspect, the NDP plays a role in forming social sensitivity and encouraging awareness of injustice through community empowerment programs. Second, in the economic aspect, the NDP encourages equitable economic development through strengthening MSMEs and the people's economy. Third, in the political aspect, the NDP is an ethical guide for cadres in strengthening democracy and good governance. Effective implementation of the NDP requires a comprehensive strategy including strengthening cadre formation, inclusive research and social action programs, as well as cross-sector collaboration.